AIRLINE TICKET RESERVATION SYSTEM AT THE COMPANY'S TRAVELING RASKHAN - Titis Susilowati; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2004)
Remember for more mengefektifitaskan any existing business activities in the wider community which is still done manually should be replaced with computer assistance and the specific programming techniques Computer using the engine should be adjusted to the abilities and needs. and in the processing of data would be more accurate, faster and not waste time and energy.